Research into different methods for measuring the particle-size distribution of aggregates: An experimental comparison. (10th October 2019) - Yang, Jian-hong; Fang, Huai-ying
Graphical abstract: Highlights: Two new measuring platforms for PSD were developed by DIM. The regression models of different PS characterization parameters are constructed. The PS has a significant influence on the measurement results of PSD. The three-dimension compensation model of PSD is constructed. The two-dimension compensation model of PSD is constructed. Abstract: The vibration-screening method (VSM) is used to measure particle-size distributions (PSDs) based on particle-penetration rate, but VSM is unable to measure the particle shapes (PSs) of aggregates. Contrarily, the digital-imaging method (DIM) measures PSDs by extracting particle contours and can simultaneously measure both the PSDs and PSs of aggregates. High measurement errors are prevalent in PSDs measured using both VSM and DIM, due to particle shape and adhesion. In this study, two different PSD-measurement techniques were developed using a camera and a laser-height-profile-measurement sensor (LHPMS). When particles were in lying and falling states, fully dispersed particle-profile parameters were extracted through backlight measuring system and a particle-image-processing algorithm. A similar algorithm, based upon DIM, was developed for PSDs. The PSDs of different materials obtained using different measurement methods were compared. For coarse aggregates, the PSDs obtained using DIM were measured in the lying state. In each case, the three-dimensional particle-shape index (PSI) of all coarse particles was measured and calculated. Coarse-aggregate PSDs were also compensated using PSI. Compared with VSM, the maximum measurement errors of PSDs compensated by DIM is 1.2%. Similar methods were used to determine fine aggregates, two-dimensional PSs were measured. Furthermore, linear-regression analysis (LRA) between PSs (i.e. the ratio of equivalent ellipse axis and sphericity) and PSI for fine aggregates was studied. The PSDs of fine aggregates were compensated. Compared with VSM, the maximum measurement error of PSDs compensated by DIM is 1.3%. We believe that our PSD-measurement accuracies have the potential to meet building and construction industry requirements.